A multiyear quality improvement project to increase influenza vaccination in a pediatric oncology population undergoing active therapy. Issue 9 (1st June 2018) - Olshefski, Randal S.; Bibart, Mindy; Frost, Randall; Wood, Eric; Hampl, Joshua; Mangum, Ross; Ardura, Monica; Guinipero, Terri; Cripe, Timothy P.
Abstract: Background: In an effort to reduce morbidity and mortality from vaccine preventable influenza infection, national consensus guidelines recommend vaccination of patients who are immunocompromised as a result of receiving cancer therapy. Quality improvement (QI) processes are a proven method used to improve vaccination rates. Procedure: We conducted a QI initiative aimed at increasing influenza vaccination in oncology patients undergoing active treatment. Primary drivers for the project focused on patient education, staff and provider education, and communication regarding vaccine‐eligible patients. We performed a retrospective analysis of influenza infection among the vaccine‐eligible population. This approach has validity at our institution because of the consistent follow‐up and hospital admission pattern of cancer patients on active therapy such that nearly all follow‐up care is delivered at our institution. Results: We successfully achieved greater than 87% vaccination of eligible patients each vaccine season (September to March). During the recommended timeframe for delivering influenza vaccine between September and December of each vaccine season, we offered the vaccine to 100% of patients on active therapy and vaccinated >90%. Barriers to success, including vaccine refusals, increased late in the vaccine season. Influenza infection was documented in 0.5–7.3% of the vaccine‐eligible group. Conclusion: A robust influenza vaccination program implemented using a standardized QI approach can sustain a high vaccination rate in a pediatric oncology population receiving active treatment. The influenza infection rate was under 10% in the vaccinated group.